EASL Clinical Practice Guidelines: Management of hepatocellular carcinoma - Galle, Peter R.; Forner, Alejandro; Llovet, Josep M.; Mazzaferro, Vincenzo; Piscaglia, Fabio; Raoul, Jean-Luc; Schirmacher, Peter; Vilgrain, Valérie (Journal of hepatology, 2018)
Liver cancer is the fifth most common cancer and the second most frequent cause of cancer-related death globally. Hepatocellular carcinoma represents about 90% of primary liver cancers and constitutes a major global health problem. The following Clinical Practice Guidelines will give up-to-date advice for the clinical management of patients with hepatocellular carcinoma, as well as providing an in-depth review of all the relevant data leading to the conclusions herein.